(3WQGR Gdce GdePgH aj GdCPcGQ GdhGQOI ef GdcJGH hGdSfIs - (3eMeO Hf CHj HcQ Hf CjhH Hf SYO GdRQYj GdOeTbj, CHh YHO Gddg, TeS GdOjf,J (B751 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ceG jfHZi dLdGd PGJg hYXje SdWGfg s
(3BNQgG (B:s
(3ajbhd Gddg JYGdi aEfi bO CYWjJg eGQLi Je GdcJGH GdeHGQc s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B106s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(200) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs